IMPROVED PRODUCTION OF TIGER SHRIMP (Penaeus monodon) THROUGH PROBIOTICS APPLICATION - Irsyaphiani Insan; Endhay Kusnendar Kontara; Raden Roro Sri Pudji Sinarni Dewi (Indonesian Aquaculture Journal, 2015)
The study was carried out in Brebes District, the North coast of Java. Tiger shrimp farming in Indonesia, particularly in this area faced some problems which caused by improper pond preparation, disease, and low seed quality. Probiotic was applied in pond to solve this problem. The aim of this study was to evaluate the production of tiger shrimp in ponds with probiotic applications. Six experimental ponds (each measuring 0.5 ha) were selected of which three were probiotic ponds and three were controlled. Tiger shrimp postlarvae (PL-30) were stocked at density of four shrimps/m2. Tiger shrimps were reared for three months. Shrimps were fed by commercial pellet. In the first month, shrimp were fed about 7%-5% of the total biomass; in the second months, 3.5%-3% of the total biomass; and in the third month, 2.5%-2% of the total biomass. The treatments in this study were the application of probiotics with concentration of 3 mg/L that were given every five days and control (without probiotics). The results showed the rearing period was 92 ± 6 days in probiotic ponds and 76 ± 16 days in controlled pond. The shrimp in controlled pond should be harvest earlier caused by the high mortality. The average final weight was 16.2 ± 0.7 g in probiotic pond and 15.6 ± 1.9 g in controlled pond. The survival rate was 64.13 ± 12.63% in probiotic pond and 44.17 ± 14.15% in controlled pond. Production was 208 ± 46 kg/pond/cycle in probiotic pond and 123 ± 6 kg/pond/cycle in controlled pond. The result showed that probiotic plays an important role in maintaining water quality parameters and health management as well as increases the survival of shrimp.